2012
DOI: 10.1093/dnares/dss024
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution in Cyanobacteria: Re-sequencing a Motile Substrain of Synechocystis sp. PCC 6803

Abstract: Synechocystis sp. PCC 6803 is a widely used model cyanobacterium for studying photosynthesis, phototaxis, the production of biofuels and many other aspects. Here we present a re-sequencing study of the genome and seven plasmids of one of the most widely used Synechocystis sp. PCC 6803 substrains, the glucose tolerant and motile Moscow or ‘PCC-M’ strain, revealing considerable evidence for recent microevolution. Seven single nucleotide polymorphisms (SNPs) specifically shared between ‘PCC-M’ and the ‘PCC-N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 50 publications
3
162
2
Order By: Relevance
“…Our very recent in vitro analysis clearly demonstrated that the KaiC1 protein of Synechocystis exhibits autophosphorylation activity and that KaiC1's kinase activity is positively affected by KaiA (53). On the other hand, laboratory substrains of Synechocystis have evolved over the course of the last 2 decades, with different phenotypes and single nucleotide polymorphisms (SNPs), but mutations in known circadian clock-related genes were not found in the Synechocystis substrain "PCC-M" used here (54). However, one has to consider that the number of previously reported circadian clockregulated genes is very small for Synechocystis.…”
Section: Discussionmentioning
confidence: 75%
“…Our very recent in vitro analysis clearly demonstrated that the KaiC1 protein of Synechocystis exhibits autophosphorylation activity and that KaiC1's kinase activity is positively affected by KaiA (53). On the other hand, laboratory substrains of Synechocystis have evolved over the course of the last 2 decades, with different phenotypes and single nucleotide polymorphisms (SNPs), but mutations in known circadian clock-related genes were not found in the Synechocystis substrain "PCC-M" used here (54). However, one has to consider that the number of previously reported circadian clockregulated genes is very small for Synechocystis.…”
Section: Discussionmentioning
confidence: 75%
“…PCC-N and Synechocystis sp. PCC-P) by Narikawa et al (2011) that contain known genetic differences from Synechocystis (Trautmann et al, 2012). Additionally, the variations in response could be caused by differences in the location of the disruption.…”
Section: Discussionmentioning
confidence: 99%
“…SynEtr1 is one of several phytochrome-like proteins identified in Synechocystis; some of these proteins, including SynEtr1, are involved in the regulation of phototaxis (Kaneko et al, 1996;Hughes et al, 1997;Yeh et al, 1997;Park et al, 2000;Wilde et al, 2002;Narikawa et al, 2011;Song et al, 2011 (Ikeuchi and Tabata, 2001;Trautmann et al, 2012), failed to move in response to directional white light in the absence or presence of ethylene, indicating that ethylene affects taxis rather than growth (data not shown). The effect of ethylene on light sensitivity also was examined by performing phototaxis assays in air and 1 mL L 21 ethylene at fluence rates ranging from 3.5 to 30 mmol m 22 s 21 white light.…”
Section: Application Of Ethylene Affects Phototaxis Via Synetr1mentioning
confidence: 99%
“…Indeed, several laboratory strains of Synechocystis sp. PCC 6803 carry one of two forms of a truncated sll1951 open reading frame (48,49), indicating that under laboratory conditions cells with a shorter Sll1951 may have a slight growth advantage.…”
Section: Discussionmentioning
confidence: 99%